Criminal Responsibility for Use of Other People's KTP in Online Loan Services - Chandra Asmoro Putro; Dewi K; Asenly L. Kambuaya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
KTP as the main requirement for applying for online loans is currently being abused. Misuse of other people's KTPs for online loan services results in losses for KTP owners who are not aware of these activities. This study aims to examine and analyze the existence of KTP in online loans along with criminal charges for misusing other people's KTPs for online loans. This type of research is normative legal research with statutory and conceptual approaches. The results of the study show that KTP as an electronic document in online loan services and misuse of other people's KTPs for online loans are snared by the ITE Law as well as the Personal Data Protection Law both alternatively and cumulatively.